1995
DOI: 10.1111/j.1530-0277.1995.tb01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Dysfunction and Cognitive Efficiency in Male and Female Alcoholics

Abstract: This study was conducted to examine the role of childhood behavioral disorders (CBDs) and residual attention deficit disorder (ADDRT) in alcohol-related cognitive dysfunction in male and female subjects. Alcoholic (n = 44 females, 56 males) and control (n = 40 females, 40 males) subjects completed assessments that included measures of CBDs, ADDRT, and cognitive and psychosocial functioning. Cognitive tests were specifically designed to assess efficiency in function. As expected, alcoholics were inferior to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 15 publications
3
41
1
1
Order By: Relevance
“…Lifetime alcohol problem severity (as measured by LAPS), was significantly correlated with poorer neurocognitive function, consistent with previous research (Brewer and Perrett, 1971;Butters et al, 1977;Glenn and Parsons, 1992;Knight and Longmore, 1994;Nixon et al, 1995;Parsons and Leber, 1981). However, an important portion of this association, as measured by proficiency, was mediated by concurrent lifetime smoking history.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Lifetime alcohol problem severity (as measured by LAPS), was significantly correlated with poorer neurocognitive function, consistent with previous research (Brewer and Perrett, 1971;Butters et al, 1977;Glenn and Parsons, 1992;Knight and Longmore, 1994;Nixon et al, 1995;Parsons and Leber, 1981). However, an important portion of this association, as measured by proficiency, was mediated by concurrent lifetime smoking history.…”
Section: Discussionsupporting
confidence: 79%
“…, which refers to an index combining speed and accuracy, has been a more sensitive measure of neurocognitive function in alcoholism than accuracy alone (Glenn and Parsons, 1992;Nixon et al, 1995Nixon et al, , 1998, and information processing proficiency impairments are reported for smokers as we noted earlier. To assess cognitive proficiency, we administered the short form of the MicroCog battery (Powell et al, 1994).…”
Section: Cognitive Proficiency-proficiencymentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, rather than a 'complete' lesion resulting in focal disconnection syndromes, alcoholism appears to be characterized by 'incomplete' lesions, in the form of degradation of cell microstructure, that are likely contributors to the mild, yet consistently observed, cognitive and motor deficits in alcoholism (for reviews, see Fein et al, 1990;Nixon, 1993;Oscar-Berman, 2000;Sullivan, 2000). In particular, alcoholism-related disruption of white matter fibers of the genu may contribute to frontal lobe pathology reported in vivo and postmortem and to neuropsychological deficits of executive functions, including processing inefficiency (De Rosa et al, 2004;Nixon et al, 1995) and problem solving (Moselhy et al, 2001;Oscar-Berman, 2000;Sullivan, 2000), typical of chronic alcoholism. Further, disruption of callosal and centrum fiber tracts may serve to limit the flexibility in pathways recruited to execute complex cognitive and motor tasks requiring the coordination of widely distributed networks.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one study, approximately 35% of treatment-seeking cocaine abusers met the DSM-IV criteria for childhood attention deficit hyperactivity disorder (19). Also, adult alcoholics report more residual-type attention deficit disorder (ADD) than controls (20). Low cognitive ability also has been shown to predict relapse after treatment at an alcohol treatment facility (21).…”
Section: Introductionmentioning
confidence: 99%